Migración, aculturación, sucesos que provocan inestabilidad cultural en la sociedad - Valarezo Rentería, Luis Andrés (2018)
The present research shows an artistic product that addressed a sociocultural problem that causes migration. Within this dilemma may irregularities were observed, one of them is the loss of identity that is caused over time. Migration has always existed, but in Ecuador it happened with great force during the beginning of the 21st century, in addition to the social, cultural and economic problems that caused thousands of Ecuadorians to migrate to other countries in search of new opportunities. Worrying about this situation, very apart from the economy, politics and social problems, migration sometimes allows adopting behaviors that affect or alter the cultural order. We give life to other cultures and not to which we belong. Along with this, other problems that cause abysmal differences in a family are annexed, but it is important and we are interested in exposing the virtues that our nation has and in this way recover our uncertainties and live with the hope that everything will be fine. Cultural identity is defined through multiple aspects that are essential for the experience of the human being. Culture and identities such as language, spirituality and behaviors are elements that allow the generation of identity relevance with features that differ from others. Day by day we realize and we are witnesses of acculturation processes that happen in our country, which are accompanied by several behaviors that are shown in citizens, for example we listen to or do things that belong to other nations. Acculturation has the characteristic of destroying the properties of a culture to a certain extent, but not completely. This is because migration forms groups of people that produce cultural exchanges and this designates a phenomenon that produces changes in the ways of speaking, dressing, etc. Acculturation behaviors have become latent in Ecuador, to the point that expressions or actions that are not ours are taken into account to replace or alternate positions that do not go according to our culture. All this has come to take strength, at such a point that it adapts quickly, but it is time to question ourselves and think about where we are going. Because identity is what differentiates us from others, that is why it is important to know and care about what we say or do, because that speaks about us. That being the case, it is good that this type of subject is tackled that is not so relevant, but on the contrary, it is something that will harm society in the long run. For this a work was elaborated to expose elements that speak of the identity of people. In addition allows to question and reflect about what we are doing as Ecuadorians before the processes of acculturation that have been taking place over time since the migration has existed as such.